TENERGY: multicenter phase II study of Atezolizumab monotherapy following definitive Chemoradiotherapy with 5-FU plus Cisplatin in patients with unresectable locally advanced esophageal squamous cell carcinoma - Hideaki Bando; Daisuke Kotani; Takahiro Tsushima; Hiroki Hara; Shigenori Kadowaki; Ken Kato; Keisho Chin; Kensei Yamaguchi; Shun-ichiro Kageyama; Hidehiro Hojo; Masaki Nakamura; Hidenobu Tachibana; et al. (BMC Cancer, 2020)
Abstract Background The standard treatment for patients with unresectable locally advanced esophageal squamous cell carcinoma (ESCC) is definitive chemoradiotherapy (CRT) using 5-FU plus cisplatin. However, complete response (CR) rates are low at 11–25%, resulting in 9–10 months of median overall survival (OS). An improved therapeutic efficacy by combining immunotherapy with radiation has been reported in patients with locally advanced non-small cell lung cancer. The results using ESCC cell lines suggest sequential treatment with anti-PD-L1 agents soon after completion of CRT is the most effective combination. Methods TENERGY trial is a multicenter, phase II, proof-of-concept study to assess the efficacy and safety of atezolizumab following definitive CRT in patients with locally advanced ESCC. The main inclusion criteria are unresectable locally advanced ESCC without distant metastasis, completion of 60 Gy of radiation plus two concomitant cycles of chemotherapy (cisplatin 70 mg/m2 on day 1 and 5-FU 700 mg/m2 on days 1–4, every 28 days), and adequate organ function. Within 6 weeks after CRT, participants will start taking 1200 mg of atezolizumab every three weeks and continue until 12 months or disease progression. The primary endpoint is the confirmed CR rate by the investigator’s assessment. Secondary endpoints include overall response rate, progression-free survival (PFS), OS, adverse events, and confirmed CR rate by central assessment. We will enroll 50 patients (40 with primary locally advanced ESCC and 10 with postoperative locoregionally recurrent ESCC). We will obtain biopsies from the primary site and will collect blood at 3 time points (before CRT, after CRT, and four weeks after the start of atezolizumab) for an exploratory biomarker study. We will analyze the phenotype of immune-competent cells, neoantigens, tumor mutational burden, PD-L1 status, and Human Leukocyte Antigen haplotyping. Discussion The synergistic efficacies of the sequential combination of CRT and atezolizumab should improve the CR rate, resulting in survival improvement for patients with unresectable locally advanced ESCC. Because CRT is a standard treatment option for patients with early stage to locally advanced ESCC, the sequential combination of CRT and atezolizumab has the potential to change the standard ESCC treatments. Trial registration UMIN000034373 , 10/04/2018 and EPOC1802 .